Spectral change of intermediate band luminescence in GaP:N due to below‐gap excitation: Discrimination from thermal activation. Issue 2 (15th November 2016) - Kamata, N.; Suetsugu, M.; Haque, D.; Yagi, S.; Yaguchi, H.; Karlsson, F.; Holtz, P. O.
Abstract : As an intermediate band (IB) originating from discrete nitrogen (N) levels is formed in GaP:N with increasing N concentration, GaP1− x N x alloy is considered to be a promising candidate for IB‐type solar cells. We studied the IB luminescence of a GaP1− x N x with 0.56% N and detected carrier recombination (CR) levels by superposing a below‐gap excitation (BGE) light of 1.17 eV. We resolved a high‐energy component of 2.15 eV in the IB luminescence, I high, from total luminescence intensity I all . With increasing the BGE density at fixed temperature of 5 K, the amount of decrease in I high was distinctly smaller than that of simple temperature rise without the BGE at the same I all value. We conclude that the observed intensity change of the IB luminescence due to the BGE comes not from thermal activation, but from optical excitation among the IB, conduction band, and CR levels in GaP1− x N x . It is of primal importance to understand CR levels toward determining their origins and eliminating them for realization of efficient IB‐type solar cells.